SARS-CoV-2 vaccine-elicited immune responses in solid organ transplant recipients - Euri Seo; Eui-Cheol Shin; Min Kyung Jung (Clinical Transplantation and Research)
Solid organ transplant recipients (SOTRs) are considered a high-risk group for coronavirus disease 2019 (COVID-19). The adaptive immune responses generated by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination include humoral and cellular immune responses. Most studies on the SARS-CoV-2 vaccine have focused primarily on humoral immunity, but cellular immunity is vital for effectively controlling progression to severe COVID-19. In SOTRs, the vaccine-induced adaptive immune response is significantly attenuated compared to the response in healthy individuals. Nevertheless, vaccinated SOTRs exhibit a reduced rate and severity of SARS-CoV-2 infection. This review aims to provide a concise overview of the current understanding of SARS-CoV-2 vaccine-induced immune responses in SOTRs.